The relationship between addiction and hikikomori tendencies: a case-control study - Muris, Peter; van de Pasch, Veerle; van Kessel, Janno; Peet, Josine (Frontiers in Psychiatry, 2023)
The present study examined the rela,onship between addic,on and hikikomori (extreme social withdrawal) symptoms. A group of clinically referred addic,on pa,ents (n = 31) and a group of age-and gender-matched non-clinical controls (n = 34) completed a selfreport scale for measuring hikikomori symptoms (the Hikikomori Ques,onnaire-25) along with some other ques,onnaires assessing substance use (frequency and severity) and quality of life. The results showed that addic,on pa,ents displayed significantly higher levels of hikikomori symptoms than the non-clinical control (Cohen's d = 3.41): 87.1% even showed such a high score that they were iden,fied as being at risk for the hikikomori syndrome (versus only 2.9% in the non-clinical control group). Correla,onal analyses revealed that within the addic,on group, the severity of the substance use problem (as quan,fied by an index of craving) correlated posi,vely with the level of hikikomori symptoms and nega,vely with quality of life. In other words, the more severe the addic,on, the more extreme the social withdrawal tendencies and the lower the quality of life. Altogether, the findings provide further support for the marked social impairments of people with substance use problems, and underline that this should be an important target of interven,on.